THE TEACHERS' CLINIC. - Kaulback, Frnak S.; Whitman, W. Tate; Dinman, Robert (The Accounting Review, 1953)
The article presents some common accounting problems and their solution. It says that in the usual textbook treatment of determination of cash distributions to partners by installments, at each distribution date the assumption is made that the assets remaining after the distribution will prove worthless. On this assumption, a worksheet is set up upon which losses equal to total remaining assets are charged to partners' capital accounts according to the profit and loss ratio with any capital deficits in turn charged to capital accounts with credit balances until there remains only capital accounts with credit balances. However, if it is recognized that for purposes of cash distributions of a partnership in liquidation the partners' loan accounts have the same status as their capital accounts and that the objective of the usual procedure is to assure that the partners will rank in order and amount of priority in accordance with the relative magnitude of their capital percentage as compared with their profit and loss percentage, it is possible to determine the order and amount of cash distributions at the outset. The article then gives different steps for calculating cash distribution with the help of an example.